Resolved and Redeemed: A New Fleck to the Evolutionary Divergence in the Genus Scomberomorus Lacepède, 1801 (Scombridae) With Cryptic Speciation - Jeena, N. S.; Rahuman, Summaya; Roul, Subal Kumar; Azeez, P. Abdul; Vinothkumar, R.; Manas, H. M.; Nesnas, E. A.; Rathinam, A. Margaret Muthu; Surya, S.; Rohit, Prathibha; Abdussamad, E. M.; Gopalakrishnan, A. (Frontiers in Marine Science, 2022)
Genus Scomberomorus, with 18 nominal species, sustains a significant heterogeneous fishery throughout its range. The sole molecular systematic study of this genus concerned the species group S. regalis, which contains the new world taxa. The species diversity of Scomberomorus in the northern Indian Ocean has not been studied at the molecular level, often leading to misidentifications. Here, novel genetic data is provided that reconfigures species boundaries from the region. We used single and multilocus data (8 mitochondrial and 3 nuclear genes) to infer phylogenetic relationships, species delimitation, and the resurrection of a time-calibrated phylogenetic tree. Our aim was also to verify the hypothesis of geographical races in S. guttatus predicated on variable vertebral counts. Interestingly, all species delimitation analyses have recovered another highly cryptic species in the nominal S. guttatus previously believed to have an Indo-Pacific distribution. Scomberomorus guttatus (Bloch and Schneider, 1801), in the sensu stricto, is redeemed from its type locality based on genetic data and is found to have a restricted distribution in the Bay of Bengal. The cryptic species, Scomberomorus aff. guttatus is resurrected here as Scomberomorus leopardus (Shaw, 1803) based on genetic evidence. S. leopardus is widespread in the Indo-Pacific and contains two major molecular operational taxonomic units (MOTUs) with a divergence threshold of over 2% between them. Our analysis suggests that vertebral counts must be coupled with other features to identify the lineages. The heterogeneity in the S. guttatus species group is discussed in relation to the ecological diversity of the region which facilitates larval recruitment and niche specialization. The results also revealed two allopatric putative species in S. commerson, primarily found in the Pacific and Indian Oceans. This study added genetic data from S. lineolatus and S. koreanus, not previously represented in the sequence repositories. Estimation of divergence time indicated that the Indo-West Pacific species group undergoes multiple diversification events besides the recent splits detected within S. leopardus.